2014 IEEE Seventh International Conference on Software Testing, Verification and Validation 2014
DOI: 10.1109/icst.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Test Case Prioritization Criteria for Software Product Lines

Abstract: Abstract-Software Product Line (SPL) testing is challenging due to the potentially huge number of derivable products. To alleviate this problem, numerous contributions have been proposed to reduce the number of products to be tested while still having a good coverage. However, not much attention has been paid to the order in which the products are tested. Test case prioritization techniques reorder test cases to meet a certain performance goal. For instance, testers may wish to order their test cases in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 27 publications
(68 reference statements)
0
60
0
Order By: Relevance
“…Some pieces of work have shown that two dissimilar test cases have a higher fault detection rate than similar ones since the former ones are more likely to cover more components than the latter [33,60]. This function favors a test suite with the most different test cases in order to cover more features and improve the rate and acceleration of fault detection.…”
Section: Coefficient Of Connectivity-density (Coc)mentioning
confidence: 99%
See 3 more Smart Citations
“…Some pieces of work have shown that two dissimilar test cases have a higher fault detection rate than similar ones since the former ones are more likely to cover more components than the latter [33,60]. This function favors a test suite with the most different test cases in order to cover more features and improve the rate and acceleration of fault detection.…”
Section: Coefficient Of Connectivity-density (Coc)mentioning
confidence: 99%
“…In our previous work [60], we adapted CoC to HCS configurations achieving good results in accelerating the detection of faults. Now we propose to measure the complexity of features in terms of the number of edges and constraints in which they are involved.…”
Section: Coefficient Of Connectivity-density (Coc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some identified testing techniques are derived from Combinatorial Interaction Testing and Search-Based Testing (Harman et al, 2014), Specification Based Testing (Scheidemann, 2006), Logic Based and various hybrid testing techniques (Perrouin et al, 2010;Hervieu et al, 2011a;Henard et al, 2013;Al-Hajjaji et al, 2014;Sánchez et al, 2014a). Due to the availability of various approaches, it is the motivation of this mapping study to collect and review those works, which leads to the first research question: Details on experiments conducted to the tool and their data sets are gathered in order to get a better understanding on the evaluation aspect of Combinatorial Interaction Testing techniques in SPL.…”
Section: Research Questionsmentioning
confidence: 99%